Volume 4: Heat Transfer, Parts a and B 2008
DOI: 10.1115/gt2008-51183
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Flow Investigation Using PIV in a Rotating Square-Sectioned Two-Pass Cooling System With Ribbed Walls

Abstract: In a 2-pass cooling system the pressure driven air flow distribution is investigated experimentally using the non-intrusive PIV Technique. The generic model as part of a complex and sophisticated cooling system consists of two square-sectioned ducts with a length of 20 diameters and an inherent 180 degree bend. The system has been investigated basically with smooth walls (case 0) and, later on, with two different kinds of ribbed walls in both legs. Ribs are applied to enhance the cooling performance; they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…As a result, local surface heat transfer and friction factor augmentation levels are often altered because of the presence of rotation. Figure 21 shows a typical turbine blade cooling passage arrangement from Elfert et al [50]. Here, a two-pass system is employed, which is rotating in an orthogonal mode, such that the flat surface which comprises the 180 ∘ bend between the two passes is parallel to the axis of rotation.…”
Section: Effects Of Rotationmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, local surface heat transfer and friction factor augmentation levels are often altered because of the presence of rotation. Figure 21 shows a typical turbine blade cooling passage arrangement from Elfert et al [50]. Here, a two-pass system is employed, which is rotating in an orthogonal mode, such that the flat surface which comprises the 180 ∘ bend between the two passes is parallel to the axis of rotation.…”
Section: Effects Of Rotationmentioning
confidence: 99%
“…Such vortex pairs are illustrated in Figure 21. Experimental evidence of Coriolis vortex pairs in rotating channels is provided by Elfert et al [50] and Bons and Kerrebrock [178] from Particle Image Velocimetry (PIV) experiments, as well as by Chen and Liou [101] from Laser-Doppler Velocimetry (LDV) experiments.…”
Section: Effects Of Rotationmentioning
confidence: 99%
See 2 more Smart Citations
“…PIV measured turbulent fluid flow in smooth-wall and 90 deg ribbed square channels with a 180 deg sharp turn for Re ¼ 30,000 was reported by Son et al [31]. Elfert et al [32] reported PIV measurements in a rotating square-sectioned two-pass cooling channel with inline and staggered 45 deg ribs at Re ¼ 50,000 under isothermal flow condition. They found that rotation influenced the 3D extension of turn induced separation bubble in the second pass.…”
Section: Introductionmentioning
confidence: 75%